Linguocultural Specifics of Cybersecurity Discursive Practices Representation in Russian Media Communication: Corpus-Assisted Approach - L. A. Kochetova; E. Yu. Ilyinova (Научный диалог, 2023)
The issue of the semantic, pragmatic and axiological specifics of cybersecurity discursive practices as it is displayed in the genres of media and online communication is considered. The novelty of the work lies in the application of the corpus linguistics methodology to the study of discourse, understood as a language-mediated social practice. The relevance of the work is due to the interest of linguistics in the study of discursive practices that shape a new social reality formed as a result of the Russian language functioning. By using the methods of corpus linguistics, the cognitive-semantic structure of discursive thesaurus, which comprise a new layer of lexical units, has been reconstructed, thematic groups of lexical units have been identified and their distribution in various genres of cybersecurity discourse has been established. It has been found that along with the terminology focused on the transfer of operational, practical knowledge about safe online practices, the texts in the corpus regularly employ lexical units with military and aggressive semantics, which indicates the contradiction between the goals of the discourse aimed at forming a positive attitude towards digital technologies, and language means employed to achieve them. It is shown that due to regular occurrence of neutral lexical units in negatively colored contexts, they develop negative evaluative connotations, which also contributes to the formation of users’ distrust of new technologies, enhances the feeling of risk, and generates anxiety and concern.